IN-SITU SCANNING ACOUSTIC MICROSCOPY OF CRACK BRIDGING IN ALUMINA - Marrow, T; Briggs, G; Roberts, S (1994)
High-resolution scanning acoustic microscopy has been used to observe crack bridging in a fine-grained polycrystalline alumina. The microscope is sensitive to the increased acoustic transmission across the crack from the interlocking and sliding asperities that cause crack shielding and -curve behaviour. Acoustic microscopy is found to be more reliable than optical microscopy for characterising crack bridging. The bridging zone size, bridge density and bridge failure strain are easily determined. The technique may be of considerable use in characterising R-curve mechanisms in a wide range of microstructures. © 1994.